2020
DOI: 10.1039/d0ra00100g
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ibuprofen solubility and skin permeation by conjugation with l-valine alkyl esters

Abstract: New ibuprofen derivatives were made via conjugation with L-valine alkyl esters (ValOR), where R was changed from an ethyl to a hexyl group. The ionic structure was confirmed using NMR and FTIR. Specific rotation, solubility in commonly used solvents, thermal properties including phase transitions temperatures, and thermal stability were also determined. The ionic structure with a protonated amine group on an L-valine ester and melting points below 100 C allowed inclusion of these ibuprofen derivatives into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 49 publications
3
103
0
Order By: Relevance
“…Using previously described a three-step method, 17 we synthesized salts of ibuprofen with L-valine alkyl esters (Scheme 1). The alkyl chain in the L-valine ester group was extended to methyl, heptyl, and octyl group (R) in comparison to the prior described C 2 -C 6 esters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using previously described a three-step method, 17 we synthesized salts of ibuprofen with L-valine alkyl esters (Scheme 1). The alkyl chain in the L-valine ester group was extended to methyl, heptyl, and octyl group (R) in comparison to the prior described C 2 -C 6 esters.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is characterized by low solubility (21 mg dm À3 at 25 C in water) and relative high lipophilicity (log P is in the range of 2.41-4.00 the value depends on the measurement method) which result in its poor permeation through the skin. [14][15][16][17][18][19][20][21] Due to the acidic nature (pK a ¼ 4.4), its solubility is dependent on the pH of the environmentit increases with increasing alkalinity: it can vary from 0.024 mg cm À3 (pH ¼ 2.2) to 14.8 mg dm À3 (pH ¼ 9.2). This is closely related to the increase in the ionization degree, which in turn determines the ability of ibuprofen to penetrate the skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factor signi cantly affecting the transport of active substances is the lipophilicity of the test compound (Yang et al 2008;Srinivas et al 2019;Ichihashi et al 2003;Casagrande et al 2007). The optimal log P coe cient (which is an indicator of the lipophilicity of the active substance) is in the range of 2 to 3 (Janus et al 2020;Haq et al 2018;Simon et al 2016). This was also con rmed in our own research, which showed that both eugenol and its ester derivatives were characterized by good permeability through the skin (log P: Eugenol 2.20 ± 0.001, EDChA 2.65 ± 0.001, ETChA 2.75 ± 0.002, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This freezing time ensured the stability of the skin barrier properties (Badran et al 2009). Before the examination, the skin was thawed at room temperature for about 30 The integrity of skin was checked one hour after its installation in the Franz diffusion chamber (SES GmbH Analyze Systeme, Germany). Skin impedance was measured using an LCR 4080 meter (Conrad Electronic, Germany) operating in parallel mode at 120 Hz (kΩ error < 0.5%).…”
Section: Skin Permeation Studies Of Eugenol and New Estersmentioning
confidence: 99%